The Radical New Perspective on Paul, Messianic Judaism and their connection to Christian Zionism - Toit, Philip La Grange Du (HTS teologiese studies, 2017)
The Radical New Perspective on Paul distinguishes between two subgroups of believers in Christ in Paul’s time: gentile believers and Jewish or Judaean believers. The same distinction is utilised in supporting contemporary Messianic Judaism, which presupposes an ongoing covenantal relationship between God and contemporary Jews that exists over and above Christianity. Many proponents of Christian Zionism, a Christian movement that envisions the Jews’ return to the land of Israel, utilise aspects of both the Radical New Perspective on Paul and Messianic Judaism in support of their beliefs. Ironically, while the Radical New Perspective on Paul is a certain product of post-holocaust theology, Christian Zionism can be perceived as a perpetuation of a kind of imperial theology that brings injustice to Palestinian people, especially in view of a post-imperial South African context. While none of these connections are inevitable, to point out the relationship between these approaches to identity serves to rethink some of the preconceived notions behind them, as well as some of the (unintended) consequences that arise from them.